Perforators of the arm to provide anatomical basis to skin flaps: A cadaveric study - Ritu Singh; Pooja Singh; Deepshikha Kori; Navneet Kumar; Arvind Kumar Pankaj; Nirupma Gupta (Wolters Kluwer Medknow Publications, 2022)
Introduction: The upper extremity is commonly involved in severe soft tissue defects that can be challenging functionally and cosmetically. Anatomical studies on skin vascularization provide developmental base for the flap nourished by perforating arteries. Perforator flaps reduce donor site morbidity and recovery time. Therefore, in case of cosmetic surgery of soft tissue defect of the arm, it is mandatory for reconstructive surgeons to have beforehand knowledge of vascular anatomy of cutaneous perforators of the arm. Hence, a study was done to evaluate the total number of perforators, distribution from bony landmarks, and pedicle length from source vessels on the medial, lateral, and posterior aspects of the arm. Methodology: The study was undertaken at the Department of Anatomy, King George's Medical University, Lucknow, on 15 upper limbs of fresh cadavers of both the sexes of adult age group. Methylene blue dye was injected into the arterial system of the arm. After one hour, perforators were visualized by incising the margins of the stained arm skin. Results: We observed that maximum numbers of perforators were contributed by direct branch of the brachial artery (49.7%), followed by superior ulnar collateral artery. Numbers of perforators on the medial aspect of the arm were maximum (52.0%), followed by lateral aspect and posterior aspect of the upper arm. Perforators supplying the posterior and lateral aspects of the arm had the maximum mean length. Conclusion: Thus, a detail understanding of position, length, and numbers of perforators of the arm helps surgeons to predefine the appropriate perforator flaps for reconstructive surgeries.